Factors Affecting Tourists Satisfaction in Candirejo Tourism Village, Indonesia - Hillary, Janne (Institut Pariwisata dan Bisnis Internasional, 2020)
Candirejo Village is a tourism village which focuses on the natural nuance of the village. The current challenge faced by Candirejo Village is how to significantly increase the number of tourists per year. In dealing with this challenge, the management should manage tourists satisfaction. The factors that need to be paid attention to the tourists' satisfaction are the attraction, facility, service, accessibility, and price. This study aims to examine and analyze the effect of attraction, facility, service, accessibility, and price on the tourist's satisfaction of Candirejo Village. The analysis results show that all of the independent variables jointly affect the tourist's satisfaction in Candirejo Village. Despite that, the price was the only factor individually affecting the tourist's satisfaction in Candirejo Village. Therefore, attraction, facility, service, accessibility, and price are multi-factors. Optimal synergized of these factors can increase the tourist's satisfaction in Candirejo Village.